Eco-physiological Studies on Gmelina arborea: I. Pre-germination Treatments and Initial Growth Developments (Biological Sciences - PJSIR, 2006)
This study examined the effects of immersion in cold water, hot water, conc H SO , vernalization and mechanical2        4scarification on the germination and initial growth development of Gmelina arborea. In the treated seeds germination wasfaster than the untreated seeds i.e. the control. While germination was first observed on 9th day after sowing in the treated seeds, in the control it took 16 days after sowing for germination. The results also showed that longer exposure of the seeds to the treatment medium might not necessarily hasten germination. The speed of germination was directly proportional to the germination percent. Manually scarified seeds had the highest germination percent %, followed by cold, hot, vernalization and acid treatments, respectively. Most seedlings from treated seeds grow better than those from the control. The early germination might be responsible for the better growth advantage.